EFFECT OF PELVIC FLOOR EXERCISE ON URINE ELIMINATION IN POSTPARTUM WOMEN - Etty Komariah Sambas; Enok Nurliawati (Journal of Maternity Care and Reproductive Health, 2019)
Physical changes of the postpartum women in the urinary system involve the elimination function of urine which involves the bladder structure. Problems with the elimination system after childbirth can occur for years if they don't get proper treatment right after delivery. This study aimed to identify the effect of pelvic floor exercise on urine elimination in postpartum women. Methods: The research design used quasi-experimental with a post-test only design approach. The sample was selected based on the inclusion criteria. Sample size were 64 people (intervention group: 32 people and the control group: 32 people). Data collection used questionnaires and self-assessment sheets. Data analysis used univariate and bivariate (Chi-square). Results:  The results showed no difference in urine elimination both urination frequency (p = 0.450) and urine flow characteristics (p = 0.519) in postpartum women who performed pelvic floor exercise and who did not carry out pelvic floor exercise. However, respondent characteristics that influenced urine elimination (urine flow characteristics) were the age (p = 0.044), parity (p = 0,000) and types of delivery (p = 0.031). Conclusion: Pelvic floor exercise which is carried out in the early postpartum period do not affect urine elimination in terms of urination frequency and urine flow characteristics. Further research on various measures aimed at strengthening pelvic floor muscles in addition to pelvic floor exercise needs to be done to reduce the problem of urine elimination in postpartum women.Keywords: Pelvic floor exercise, urine elimination.